Soybean Bradyrhizobium spp. Spontaneously Produce Abundant and Diverse Temperate Phages in Culture - Vanessa A. Richards; Barbra D. Ferrell; Shawn W. Polson; K. Eric Wommack; Jeffry J. Fuhrmann (Viruses)
Soybean bradyrhizobia (Bradyrhizobium spp.) are symbiotic root-nodulating bacteria that fix atmospheric nitrogen for the host plant. The University of Delaware Bradyrhizobium Culture Collection (UDBCC; 353 accessions) was created to study the diversity and ecology of soybean bradyrhizobia. Some UDBCC accessions produce temperate (lysogenic) bacteriophages spontaneously under routine culture conditions without chemical or other apparent inducing agents. Spontaneous phage production may promote horizontal gene transfer and shape bacterial genomes and associated phenotypes. A diverse subset (n = 98) of the UDBCC was examined for spontaneously produced virus-like particles (VLPs) using epifluorescent microscopy, with a majority (69%) producing detectable VLPs (>1 × 107 mL−1) in laboratory culture. Phages from the higher-producing accessions (>2.0 × 108 VLP mL−1; n = 44) were examined using transmission electron microscopy. Diverse morphologies were observed, including various tail types and lengths, capsid sizes and shapes, and the presence of collars or baseplates. In many instances, putative extracellular vesicles of a size similar to virions were also observed. Three of the four species examined (B. japonicum, B. elkanii, and B. diazoefficiens) produced apparently tailless phages. All species except B. ottawaense also produced siphovirus-like phages, while all but B. diazoefficiens additionally produced podovirus-like phages. Myovirus-like phages were restricted to B. japonicum and B. elkanii. At least three strains were polylysogens, producing up to three distinct morphotypes. These observations suggest spontaneously produced phages may play a significant role in the ecology and evolution of soybean bradyrhizobia.